PAPR reduction using polynomial based compressing with Rapp model in GFDM - P.V. Naganjaneyulu; U. Sreenivasulu; M. Nageswara Rao; G. Sujatha (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
Generalized Frequency Division Multiplexing (GFDM) has been considered as an attractive candidate to replace Orthogonal Frequency Division Multiplexing (OFDM) for the fifth generation (5 G) mobile networks. GFDM system has better spectral characteristics compared to the OFDM system due to the usage of properly selected pulse shaping filters. Non-causal ideal filters, such as the raised cosine (RC), are commonly used in the GFDM systems. Here, Generalized frequency division multiplexing is a promising candidate to deploy. However, as an intrinsic property of multi-carrier modulation, the high signal amplitude fluctuation can cause several degradation effects when the signal is affected by nonlinearities. The pulse shaping filters are designed using the computationally efficient quadratic programming (QP) approach. Therefore, the aim of this paper is to evaluate the performance of Generalized frequency division multiplexing systems undergoing nonlinear amplification. We evaluate the bit error ratio using high power amplifier, namely the Rapp model. The results show that the fault rate is apparently affected according to the particular high power amplifier model and its transmission parameters.